Clonal propagation of coconut using axillary in vitro shoots: Merits of the technology, potency and progress - Panis, Bartholomeus; Wilms, Hannes (2022)
Proceedings of 50th International Cocotech Conference and Exhibition 2022 (COCOTECH 2022) November 7-11, Kuala Lumpur